THE APPLICATION OF THE GUIDE CODE OF CONDUCT FOR MUSLIM TOUR LEADERCOMMUNITIES DURING THE COVID19 PANDEMIC - Akbar, Mochamad Fajar; Bahri, Asep Syaiful (Journal of Indonesian Tourism and Policy Studies, 2020)
Research on the application of the guide code of conduct for Muslim tour leader communities during the Covid19 pandemic is to determine the strategy for implementing the guide code of ethics for Muslim tour leader communities during the Covid19 pandemic. The sample in this study is the Muslim tour leader community, amounting to 200 respondents. The data analysis method used in this research is descriptive method using Importance performance analysis. Based on the survey results, there is an average value of the level of importance is 8.19 and the average value of the level of need is 7.39. This indicates that the overall application of the code of conduct for tourism has a high level of importance and also has a high level of need. The results of this study indicate that the application of the guide code of ethics during the Covid19 pandemic is in quadrant 1 (frst priority), quadrant 2 (keep it) and quadrant 4 (leave it).